Assessing Change Management and Performance of Selected Banks in Anambra State, Nigeria - Ezeanokwasa Francisca Nkiru; Nwagbala Stella Chinelo; Nwachukwu Raphael (Research Parks Publishers, 2023)
The continuous resistance to change by employees has resulted in survival problem of Banks as the banking industry seems to experience technological and environmental change. In view of this, this study determined the relationship that exists between change management and selected Banks in Anambra State. The study adopted descriptive survey research design and Purposive Sampling Technique was used to select 3 notable banks operating in the major cities of Anambra State that is Nnewi, Awka and Onitsha, these banks Include; branches of Fidelity Bank Plc, Access Bank Plc, and Eco Bank plc, operating at Awka, Onitsha and Nnewi, Anambra State. Data were collected from 162 respondents with the aid of structured questionnaire. Personal Data of respondents were presented using simple frequency and percentage tables. Data relating to research questions were analyzed using Descriptive Statistics (Arithmetic Mean). Hypotheses were tested using Pearson Product Moment Correlation Coefficient with the aid of Statistical Packages of Social Science (SPSS version 23). Findings revealed that there is significant relationship between change management and organizational performance of selected Banks in Anambra State by indicating positive relationship between internal communication and business sustainability; positive relationship between employee development and business competitiveness; the study concluded that change management is a remedy to employee resistance to change. The study recommended that management should adopt supportive approach while introducing change into the organization.